Демократизація виборчого законодавства як фактор становлення громадянського суспільства в Україні - Довбня, О.М.; Dovbnya, O.; Довбня, О.М. (Харківський національний університет імені В.Н.Каразіна, 2012)
Розглядається проблема взаємодії виборчого законодавства та активності населення. Доводиться необхідність удосконалення виборчого процесу у напрямку посилення активного начала – механізму волевиявлення громадян й контролю за виборними органами та представниками. The problem of interaction of suffrage and population’s activity is examined. The necessity of improvement of electoral process in the direction of intensification of active position is given, as well as the mechanism of expression of the electors' will and control over electoral authorities and representatives.
Democratization of electoral legislation as a factor of development of civil society in Ukraine
Keywords: громадянське суспільство; виборча система; активне виборче право; пасивне виборче право; процеси самоорганізації; громадські ініціативи; electoral system; processes of self-organization; civil initiatives; civil society; eligibility; positive suffrage